The effect of replacement of wheat bran by graded levels of molasses on feed intake, organic matter digestion, rumen fermentation and nitrogen utilization in crossbred (Bos taurus X Bos indicus) steers fed native grass hay - Osuji, P.O.; Khalili, H. (1994)
The paper evaluates the effect of replacement of wheat bran by graded levels of sugar cane molasses on feed intake, rumen fermentation and nitrogen utilization. Four ruminally fistulated crossbred (Bos taurus X Bos indicus) steers were given a basal diet of grass hay ad libitum and 4.0 kg dry matter of wheat bran. In the other three diets wheat bran was replaced with molasses. Urea supplementation was used to make the three diets isonitrogenous with the basal diet. The voluntary dry matter intake of hay was not affected significantly by the treatments. The apparent digestibility of organic matter was similar between diets. Molasses did not depress significantly the average value of rumen PH. Increasing the level of molasses increased mainly the molar proportion of propionate at the expense of acetate. Apparent digestibility of nitrogen was similar between diets. Daily excretion of allantoin in the urine was not affected by molasses. There was a quadratic effect caused by molasses so that with the two diets the daily excretion of uric acid was higher compared with the other two diets. Total microbial purine derivatives and microbial nitrogen were not significantly different between diets.